2020
DOI: 10.3390/cancers12030717
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Murine Rnaset2 in a Colon Syngeneic Mouse Carcinoma Model Leads to Rebalance of Intra-Tumor M1/M2 Macrophage Ratio, Activation of T Cells, Delayed Tumor Growth, and Rejection

Abstract: Human RNASET2 acts as a powerful oncosuppressor protein in in vivo xenograft-based murine models of human cancer. Secretion of RNASET2 in the tumor microenvironment seems involved in tumor suppression, following recruitment of M1-polarized macrophages. Here, we report a murine Rnaset2-based syngeneic in vivo assay. BALB/c mice were injected with parental, empty vector-transfected or murine Rnaset2-overexpressing mouse C51 or TS/A syngeneic cells and tumor growth pattern and immune cells distribution in tumor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Previously, polarized TAMs were recognized with oversimplified terms such as M1 macrophages and M2 macrophages based on the cell polarization concept of helper T cell type 1 and type 2 6,10,11 . However, with accumulating in vivo data from the studies of inflammatory diseases including cancer demonstrated that macrophage polarization is the representation of continuum of diverse functional state [6][7][8] . Therefore, currently the terms M1-like macrophages and M2-like macrophages are used to describe the phenotypes of polarized macrophages 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, polarized TAMs were recognized with oversimplified terms such as M1 macrophages and M2 macrophages based on the cell polarization concept of helper T cell type 1 and type 2 6,10,11 . However, with accumulating in vivo data from the studies of inflammatory diseases including cancer demonstrated that macrophage polarization is the representation of continuum of diverse functional state [6][7][8] . Therefore, currently the terms M1-like macrophages and M2-like macrophages are used to describe the phenotypes of polarized macrophages 9 .…”
Section: Discussionmentioning
confidence: 99%
“…As evolutionarily conserved tumor suppressors, T2 RNases can inhibit tumor growth in vivo by balancing the M1/M2 macrophage ratio in tumors and recruiting adaptive antitumor CD8 + T cells [143]. Furthermore, Halama, N. and his colleagues also confirmed that inhibiting CCR5 can repolarize the phenotype of TAMs from M2 to M1 by regulating the STAT3/SOCS3 signaling pathway in TAMs, thereby exerting antitumor effects in a phase I clinical trial of patients with CRC liver metastases [144].…”
Section: Repolarizing Tamsmentioning
confidence: 94%
“…Noteworthy, a murine Rnaset2 syngeneic murine model was also recently reported by using mouse Rnaset2 -overexpressing C51 colon carcinoma and TS/A mammary adenocarcinoma syngeneic cells in comparison to control empty vector-transfected tumor cells [ 50 ]. Although the reported in vivo study was mainly focused on the C51 cancer cell model, a trend for a Rnaset2-mediated tumor suppressive effect was observed in TS/A cells as well [ 50 ].…”
Section: Non-cell-autonomous Roles Of Rnaset2 As a Tumor Suppressor Genementioning
confidence: 99%
“…Noteworthy, a murine Rnaset2 syngeneic murine model was also recently reported by using mouse Rnaset2 -overexpressing C51 colon carcinoma and TS/A mammary adenocarcinoma syngeneic cells in comparison to control empty vector-transfected tumor cells [ 50 ]. Although the reported in vivo study was mainly focused on the C51 cancer cell model, a trend for a Rnaset2-mediated tumor suppressive effect was observed in TS/A cells as well [ 50 ]. Of note, in the in vivo C51-based syngeneic model, a strong Rnaset2 -dependent retardation in tumor growth rate was observed, concomitant with early tumor infiltration by M1 macrophages, inhibition of M2 and myeloid-derived suppressor cells (MDSCs) cells and, very interestingly, a later expansion of CD8 + T lymphocytes with rejection capacity and antitumor recall immunity [ 50 ].…”
Section: Non-cell-autonomous Roles Of Rnaset2 As a Tumor Suppressor Genementioning
confidence: 99%